Digital Education Management in Improving the Quality of Technology-Based Learning - Husnaini, Azizah Nurul; Lucio Marcal Gomes; Mashudi Rofik; Jakoep Ezra Harianto; Moch. Edy Purwanto (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This study aims to explore the role of Digital Education Management Systems (DEMS) in improving the quality of technology-based learning. Using a qualitative method with a library research approach, this research analyzes various theories, models, and previous studies related to the integration of technology in education management. The findings indicate that DEMS play a crucial role in enhancing educational quality by streamlining administrative tasks, facilitating personalized learning, and supporting data-driven decision-making. Additionally, digital leadership is found to be essential in ensuring the effective implementation of DEMS, fostering a culture of innovation and continuous improvement within educational institutions. However, challenges such as digital infrastructure limitations, resistance to technology adoption, and the digital divide remain barriers that must be addressed for optimal implementation. This study suggests the need for equitable access to technology and the professional development of educators and leaders to improve their digital literacy. Overall, while DEMS hold great potential to enhance technology-based learning, their successful implementation heavily depends on overcoming the existing barriers. Future research is recommended to further investigate strategies to bridge the digital divide and evaluate the long-term impact of DEMS on student learning outcomes.